KERAGAMAN TANAMAN BERKHASIAT OBAT DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) RANTAU - Dina Naemah; Eny Dwi Pudjawati (Lambung Mangkurat University-Indonesia, 2021)
One of the forest uses other than wood and the environment is a source of medicinal ingredients. Medicinal substances of natural origin are simplicia. Simplicia is simple plant material, not mixed with other plant parts, for example seeds, leaves, tubers, roots and stems. Communities around the forest area are an important source of information to determine the benefits of plants used for treatment, such as identification of plant species, plant parts used, and processing methods. The purpose of this activity is to inventory the types of medicinal plants and analyze their benefits. The method used is the analysis of vegetation at three locations, secondary forest, grass (Imperata cylindrica) land and plantation forest. Data obtained from the field and interviews with the community. There are 16 species of medicinal plants at all growth levels in the study site. The largest level of mastery of Vitex pinnata species (trees and poles, saplings and seedlings) and undergrowth is that of Imperata cylindrica. Diversity index of medicinal plants is in the low to moderate criteria. The part of the plant that is used the most is the root.